Analysis of System Quality, Information Quality, and Service Quality on E-Filing User Satisfaction - Nur Magfira Awaliah.F; Kartini; Grace T. Pontoh (MultiTech Publisher, 2024)
E-filing is a tax reporting system using an Annual Tax Return (SPT) that is conducted electronically. This study aims to test and analyze the success of the e-Filing system using the Information System Success Model approach by DeLone & McLean (2003). The data used in this study is primary data collected through questionnaires, with a total sample of 70 individual taxpayers registered as employees at the Bulukumba Tax Office. The measurement variables used include system quality, information quality, service quality, and user satisfaction. The results show that information quality has a positive and significant effect on user satisfaction, and service quality also has a positive and significant effect on user satisfaction. This research can contribute to tax authorities in developing electronic systems to facilitate taxpayers in filing their tax returns. It also highlights the importance of information quality and service quality in the use of the e-filing system to ensure that taxpayers feel satisfied in fulfilling their tax obligations.